Comparative Proximate Analysis between Two Types of Moringa (Moringa Oleifera and Moringa Ovalifolia) - Gafai, Ibrahim Usman; Darma, Maryam Lawal (International Journal of Scientific Research in Biological Sciences, 2024)
Moringa oleifera and Moringa ovalifolia are highly valued for their nutritious seeds and are often consumed in sub-Saharan Africa. Different parts of these plants have a profile of key minerals and are high in protein, vitamins, B-carotene, and amino acids. Moringa leaves contain vitamins A, calcium, iron, C, and potassium. Moringa oleifera is well-known for its high nutritional content, which has been likened to that of Moringa ovalifolia. Moringa oleifera, also known as "Zogale" in Northern Nigeria, is one of the most widely distributed and cultivated plant species in the region. However, the prospective uses for their leaves were not adequately researched and documented. As a result, proximal examination of their leaves for possible applications is extremely important. Leaf samples were collected from Nigeria`s Katsina metropolis and analyzed for proximate components using standard analytical methods. Moringa oleifera and moringa ovalifolia leaves had percentage carbohydrate, crude fiber, and moisture contents of 56.33±0.29, 63.11±0.11, 11.23±0.16, 7.09±0.11, 10.74±0.05, and 2.11±0.11, respectively. Moringa oleifera and moringa ovalifolia leaves had crude protein, lipid, and ash levels of 9.38±0.23, 17.1±0.1, 7.76±0.21, and 1.69±0.09, 10.74±0.05, and 2.11±0.11, respectively. Moringa oleifera leaves had more crude fiber, lipid, and moisture content than moringa ovalifolia leaves, whereas moringa ovalifolia leaves had much higher protein, ash, and carbohydrate content.